Probability-Based Sensitivity of Service Life of Chloride-Attacked Concrete Structures with Multiple Cover Concrete Repairs - Aruz Petcherdchoo (Advances in Civil Engineering)
This paper presents probabilistic and sensitivity analysis of service life (or time to repairs) for attaining corrosion-free condition of concrete structures under chloride attack. Four groups of probabilistic parameters are determined, i.e., (1) time-dependent chloride content, (2) mean and median of corrosion initiation and repair application times, (3) percent confidence of repairs, and (4) total expected number of repairs. To achieve this, this paper proposes a computational approach and probabilistic data. The proposed approach, which combined the Latin Hypercube technique with the Crank–Nicolson-based finite difference approach, is developed for predicting probabilistic chloride diffusion in concrete with repairs by cover concrete replacement. Probabilistic data of four governing random variables (surface chloride, diffusion coefficient, concrete cover depth, and critical chloride) and six repair strategies for corrosion-free condition are introduced. Numerical assessment is then shown. From the study, it is revealed that the reduction of the amount of chloride ions at the threshold depth due to using higher depth of cover concrete repairs is better than that using higher quality of repair materials. However, the excessive depth of repairs is not always recommended due to another control factor, such as the immediate amount of chloride ions at the repair depth, cost of repairs, etc. From the sensitivity analysis, the cover depth is found to be the most important parameter in the design of chloride-attacked concrete structures to extend the corrosion initiation and repair application times and to reduce the total expected number of repairs.